2008
DOI: 10.1007/s11274-008-9880-6
|View full text |Cite
|
Sign up to set email alerts
|

Xylanase production using inexpensive agricultural wastes and its partial characterization from a halophilic Chromohalobacter sp. TPSV 101

Abstract: A halophilic and alkali-tolerant Chromohalobacter sp. TPSV 101 with an ability to produce extracellular halophilic, alkali-tolerant and moderately thermostable xylanase was isolated from solar salterns. Identification of the bacterium was done based upon biochemical tests and 16S rRNA sequence. The culture conditions for higher xylanase production were optimized with respect to NaCl, pH, temperature, substrates and metal ions and additives. Maximum xylanase production was achieved in the medium with 20% NaCl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Likewise, Chromohalobacter sp. TPSV 101 isolated from the solar salt pans showed the optimum xylanase activity even at 20% NaCl concentration (Prakash et al, 2009). It was reported that metal ions are activators of enzymes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Likewise, Chromohalobacter sp. TPSV 101 isolated from the solar salt pans showed the optimum xylanase activity even at 20% NaCl concentration (Prakash et al, 2009). It was reported that metal ions are activators of enzymes.…”
Section: Resultsmentioning
confidence: 97%
“…Hpl-002 , Bacillus halodurans (Kumar and Satyanarayana, 2011) B. pumilus GESF-1 (Menon et al, 2010), B. subtilis ASH (Sanghi et al, 2010), Chromohalobacter sp. TPSV (Prakash et al, 2009), Bacillus sp. GRE7 (Kiddinamoorthy et al, 2008), Cellulomonas xavigena (Santiago-Hernández et al, 2007), Enterobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…Species of these two genera have already been identified for the capability to degrade hemicelluloses (Govender et al 2009; Kui et al 2010; Prakash et al 2009). The strains phylogenetically most related to an uncultured clone from the microbiome showed an individual variation, some being positive and some negative in the cellulolytic test (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…b-xylanases (bÀ1,4-D-xylan xylanohydrolase, EC 3.2.1.8) and b-xylosidases (1,4-b-D-xylan xylohydrolase, EC 3.3.1.37) are involved in the hydrolysis of the xylan [241]. Xylanases hydrolyze xylans to produce mixtures of xylooligosaccharides which can be the substrates for bxylosidases for further hydrolysis [242].…”
Section: Lipases and Esterasesmentioning
confidence: 99%